Malrotation in Congenital Diaphragmatic Hernia: Is It Really a Problem? - Heiwegen, Kim; de Blaauw, Ivo; van Ling, Julia; Botden, Sanne M. B. I. (European Journal of Pediatric Surgery, 2019)
Introduction Congenital diaphragmatic hernia (CDH) has been associated with other congenital malformations, such as intestinal rotation abnormalities. However, there is no standard evaluation and treatment of intestinal rotation during initial CDH repair. This study evaluates intestinal malrotation in CDH patients.Materials and Methods All patients with a CDH treated in a high-volume center between 2000 and 2015 were retrospectively evaluated. Demographics, gastrointestinal characteristics, surgical treatment, and abdominal outcomes (acute surgery, small bowel obstruction, and volvulus) were described.Results A total of 197 CDH patients were surgically repaired. In 76 (39%) patients, a malrotation was described at initial CDH repair, in 39 (20%) patients, a normal rotation, but 82 patients (42%) had no report on intestinal rotation. During follow-up (range: 2–16 years), 12 additional malrotations were diagnosed, leading to a prevalence of at least 45% (n = 88). These were mostly diagnosed due to acute small bowel obstruction, of which three had a volvulus. Of the 12 later diagnosed malrotations, 58% required acute surgery, compared to 3% of the 76 initially diagnosed patients (p < 0.001).Conclusion Malrotation is associated with CDH, with a prevalence of at least 45% and in 21% a normal intestinal rotation. “Missed” malrotations have a higher risk on need for acute surgery later in life.
Keywords: congenital diaphragmatic hernia; malrotation; small bowel obstruction